Mekanisme Pertahanan Konflik Dalam Novel Tak Sempurna Karya Fahd Djibran: Tinjauan Psikologi Sastra Dan Implementasinya Sebagai Bahan Ajar Sastra Di Smp Muhammadiyah Darul Arqom Karanganyar - Wijayanto, Nur; , Dra. Main Sufanti, M. Hum (2015)
ABSTRACT DEFENSE MECHANISM OF CONFLICT IN THE TAK SEMPURNA NOVEL BY FAHD DJIBRAN: LITERATURE PSYCHOLOGICAL REVIEW AND IMPLEMENTATION AS LITERARY LEARNING MATERIAL IN SMP MUHAMMADIYAH DARUL ARQOM, KARANGANYAR Nur Wijayanto, A 310 100 034. Indonesian Program Study, Teacher Training and Education Faculty, Muhammadiyah University of Surakarta, 2015, 91 pages Purposes of the research are to: (1) describe unique literary characteristics of Fahd Djibran, (2) depict constructive structure of Tak Sempurna novel, (3) explain conflict manifestation found in selves of the characters, (4) expose defense mechanism of conflict raised by the characters, (5) explain implementation of results of the research as literary learning material in SMP Muhammadiyah Darul Arqom of Karanganyar. The research is a qualitative-descriptive one. Object of the research is defense mechanism of conflict. Primary data of the research is Tak Sempurna novel. The data consists of words, sentences, and paragraphs referring to defense mechanism of conflict in the Tak Sempurna novel. The data was collected by using literature technique, making notes and observation. The data was examined for its validity by using data triangulation technique. Hermeneutic and heuristic reading methods were used to analysis the data. Results of the research were: (1) literary unique characteristics of Fahd Djibran were, among the others, the use of figurative and inspirative languages, and often citing philosophers' or other writers' ideas; (2) Structure of the novel by Fahd Djibran was, among the others, (a) theme of the novel was a fading character of students so that they fell into bad behaviors easily, (b) storyline used chorological plot, (c) characterization consisted of main character, Rama, and additional characters, namely Heru, Eko, Tantri, papa and mama, (d) the novel used Jakarta as a place setting, years of 2010 to 2012 as a time setting, condition of school students in their labile condition as social background, (e) viewpoint of the writer was an bewitched at first sight; (3) conflicts occurred within selves of the characters were caused by their ids and superegos; (4) six defense mechanisms of conflict were found, namely (a) apathetic, (b) rationalization, (c) aggression, (d) diversion, (e)formation reaction, and (f) sublimation; (5) results of the research can be implemented as literary material learning in SMP Muhammadiyah Darul Arqom, Karanganyar in learning of a novel appreciation, a novel synopsis, constructive structure of a novel, conflict formed between characters of a novel, and defense mechanisms of conflict. Key words: defense mechanism of conflict, literature psychology